Constrictive pericarditis: Haemodynamics in a nutshell - Lubbe, W.; Herbst, P.G.; Doubell, A.F. (SA Heart Journal, 2017)
A 41-year-old male presented with predominantly right heart failure symptoms due to suspected constrictive pericarditis (CP).